Fullerene-modified transition metal hydroxide nano array material as well as preparation method and application thereof

By modifying the transition metal hydroxide nanoarray material through fullerene, the problems of poor catalytic activity and low mass transfer efficiency in organic electrostatic oxidation are solved, and the efficient catalytic and excellent mass transfer performance of the material are achieved.

CN119710811AActive Publication Date: 2025-03-28SUN YAT SEN UNIV

Patent Information

Application Number
CN202510094155.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-28
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

Existing non-precious metal-based materials have poor catalytic activity and low mass transfer efficiency in organic electro-oxidation, which limits their large-scale application in actual production.

Method used

By preparing fullerene modified transition metal hydroxide nanoarray materials, the surface electronic structure of the material is optimized using the strong electron-absorbing ability of fullerene, and the adsorption and enrichment of organic substrates are promoted through conjugated π bonds and hydrophobic action.

Benefits of technology

It achieves good catalytic activity and excellent mass transfer efficiency of the material, improves the Faraday efficiency of the organic electro-oxidation reaction, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005252397350000011
    Figure HDA0005252397350000011
  • Figure HDA0005252397350000012
    Figure HDA0005252397350000012
  • Figure HDA0005252397350000021
    Figure HDA0005252397350000021
Patent Text Reader

Abstract

The invention belongs to the technical field of organic electro-oxidation electrode materials, and particularly relates to a fullerene modified transition metal hydroxide nano array material as well as a preparation method and application thereof. A transition metal hydroxide nano array grows in situ on a current collector through solvothermal reaction, surface amino modification is achieved by means of grafting of a silane coupling agent with amino, and finally the transition metal hydroxide nano array material with the surface modified by fullerene is obtained through addition reaction of amino and fullerene carbon-carbon double bonds. The strong electron-withdrawing capability of the fullerene is beneficial to optimizing the surface electron structure of the material, so that the intrinsic catalytic activity is improved; meanwhile, fullerene can promote adsorption and enrichment of an organic substrate on the surface of the material through a conjugated pi bond, a hydrophobic effect and the like, so that the mass transfer efficiency is improved. Benefited from the lifting mechanism, the obtained nano array material has the advantages of high electrocatalytic activity and high mass transfer efficiency, and can be widely applied to a series of organic electrooxidation reactions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of organic electro-oxidation electrode materials, and more specifically to a fullerene-modified transition metal hydroxide nano-array material, a preparation method and application thereof. Background Art

[0002] In the context of increasingly severe energy crisis and environmental problems and the imperative to achieve the "dual carbon" goal, the development of efficient, economical, safe and sustainable synthesis methods is becoming increasingly important for research in the field of organic synthesis. Organic electro-oxidation uses "greener" electrons to replace traditional chemical oxidants to convert organic substrates such as alcohols, aldehydes, ketones, and amines into high-value-added organic products through electro-oxidation, overcoming the shortcomings of traditional organic chemical industry, such as serious environmental pollution, low product purity, and harsh reaction conditions, and has good development potential and application prospects. In the field of organic electro-oxidation, precious metal-based catalysts (such as Pt, Pd, Au, etc.) have attracted much attention due to their excellent catalytic performance. For example, Si et al. prepared a PdAg alloy (PdAg / NF) material grown on nickel foam and used it for electrocatalytic oxidation of ethylene glycol to produce glycolic acid by coupling hydrogen evolution, and obtained glycolic acid and high-purity hydrogen efficiently (Di Si, Bingyan Xiong, Lisong Chen, Jianlin Shi. Highly selective and efficient electrocatalytic synthesis of glycolic acid incoupling with hydrogen evolution [J]. Chem Catalysis, 2021.). Although it has a high Faraday efficiency, the high cost and scarcity of the precious metals used limit its large-scale application in actual production. Therefore, it is of great application value to develop organic electro-oxidation catalysts with high activity, stable performance and low cost based on abundant non-precious metal elements.

[0003] At present, transition metal-based catalysts such as Co and Ni are widely used in the field of organic electro-oxidation, but the performance of most of these materials is still not comparable to that of precious metal-based materials. The main limiting factors are the insufficient catalytic activity caused by the poor electronic structure of the material and the slow mass transfer kinetics caused by the low diffusion coefficient of the organic substrate in the electrolyte solution. Therefore, based on the design strategy of regulating the electronic structure of the material and improving the mass transfer efficiency, the development of transition metal-based catalytic materials with high catalytic activity and fast mass transfer efficiency will be conducive to the further promotion of organic electro-oxidation technology. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of poor catalytic activity and low mass transfer efficiency of existing non-precious metal-based materials for organic electro-oxidation, and to provide a fullerene-modified transition metal hydroxide nanoarray material with good catalytic activity and excellent mass transfer efficiency.

[0005] The purpose of the present invention is to provide a method for preparing a fullerene-modified transition metal hydroxide nanoarray material.

[0006] Another object of the present invention is to provide the application of the fullerene-modified transition metal hydroxide nanoarray material in organic electro-oxidation reaction.

[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] The present invention provides a method for preparing a fullerene-modified transition metal hydroxide nanoarray material, comprising the following steps:

[0009] S1. Preparation of transition metal hydroxide nanoarrays;

[0010] S2. placing the transition metal hydroxide nanoarray obtained in step S1 in an amino-containing silane coupling agent solution for grafting modification and post-treatment to obtain a transition metal hydroxide nanoarray material with surface amino modification;

[0011] S3. placing the transition metal hydroxide nanoarray material with surface amino groups modified obtained in step S2 in a fullerene-containing solvent, performing fullerene modification, and post-processing to obtain a fullerene-modified transition metal hydroxide nanoarray material.

[0012] The present invention realizes surface amino modification by grafting transition metal hydroxide nanoarray with silane coupling agent having amino group, and further obtains transition metal hydroxide nanoarray material with surface fullerene modification by addition reaction of amino group and fullerene carbon-carbon double bond.

[0013] The fullerene-modified transition metal hydroxide nanoarray material of the present invention has good catalytic activity and excellent mass transfer efficiency. On the one hand, the fullerene modified on the surface of the nanoarray material has a strong electron-withdrawing ability, which is beneficial to optimize the electronic structure of the material surface, thereby improving the catalytic activity; on the other hand, the fullerene can promote the adsorption and enrichment of organic substrates on the surface of the catalytic material through conjugated π bonds and hydrophobic effects, thereby improving the mass transfer efficiency.

[0014] The preparation method of the present invention is economical, fast and can be mass-produced, which is conducive to the promotion and application of the obtained nanoarray material in the field of organic electro-oxidation.

[0015] Preferably, in step S1, the specific steps of preparing the transition metal hydroxide nanoarray are: placing the current collector in a mixed solution containing a transition metal salt and a precipitant, performing a solvothermal reaction, and post-treating to obtain the transition metal hydroxide nanoarray.

[0016] The present invention places the current collector in a mixed solution containing a transition metal salt and a precipitant, mixes them evenly, and then performs a solvent thermal reaction to obtain a transition metal hydroxide nano array grown in situ on the current collector.

[0017] Preferably, in steps S1 to S3, the post-treatment is washing and drying.

[0018] Preferably, in step S1, the transition metal in the transition metal salt is selected from at least one of Ni, Fe, Co, Cu, Zn, Mn, Mo, V, Ce, W, Ti, Zr, Cr, Sc, and Y. Ni, Fe, Co, Cu, Zn, and Mn are common transition metals with catalytic activity in the field of organic electro-oxidation, while Mo, V, Ce, W, Ti, Zr, Cr, Sc, and Y are some conventional dopants, and appropriate doping is beneficial to improving the activity of the catalytic material.

[0019] More preferably, in step S1, the transition metal in the transition metal salt is a main transition metal, or a main transition metal and a doped transition metal; the main transition metal is selected from at least one of Ni, Fe, Co, Cu, Zn, and Mn; and the doped transition metal is selected from at least one of Mo, V, Ce, W, Ti, Zr, Cr, Sc, and Y.

[0020] Furthermore, in step S1, when the transition metal in the transition metal salt is a main transition metal and a doped transition metal, the molar ratio of the doped transition metal to the main transition metal is 1:(1-100); specifically, it can be 1:1, 1:9, 1:19, 1:49, 1:69, 1:89, 1:99, 1:100, etc., or an interval range formed by any of the above ratios, such as 1:(1-9), 1:(1-19), 1:(1-99), etc., but the present invention is not limited thereto.

[0021] Preferably, in step S1, the transition metal salt is selected from one or more of nitrates, acetates, sulfates, carbonates and chlorides.

[0022] Preferably, in step S1, the concentration of the transition metal salt in the mixed solution is 1 to 10000 mM. More preferably, the concentration of the transition metal salt in the mixed solution is 10 to 5000 mM, specifically 10 mM, 100 mM, 500 mM, 1000 mM, 3000 mM, 5000 mM, etc., or an interval range formed by any of the above values, such as 10 to 100 mM, 10 to 500 mM, 10 to 3000 mM, etc., but the present invention is not limited thereto.

[0023] Preferably, in step S1, the precipitant is selected from at least one of potassium hydroxide, sodium hydroxide, sodium carbonate, sodium bicarbonate, ammonia water, hexamethylenetetramine, urea and sodium oxalate.

[0024] Preferably, in step S1, the molar ratio of the transition metal salt to the precipitant is 1:(1-20). More preferably, the molar ratio of the transition metal salt to the precipitant is 1:(1-16); specifically, it can be 1:1, 1:2, 1:4, 1:8, 1:16.

[0025] Furthermore, in step S1, the current collector is a metal current collector, carbon cloth or carbon paper. Preferably, the metal current collector is metal foam, metal foil, metal plate or metal mesh, and the metal of the metal current collector is Fe, Co, Ni, Cu, Zn, Al, Ti or stainless steel.

[0026] Furthermore, in step S1, the temperature of the solvothermal reaction is 50-250° C. Preferably, the temperature of the solvothermal reaction is 60-200° C., and specifically can be 60° C., 80° C., 100° C., 120° C., 150° C., 180° C., 200° C.

[0027] Preferably, in step S1, the solvent thermal reaction time is 1 to 96 hours. Specifically, the solvent thermal reaction time is 1 hour, 2 hours, 5 hours, 8 hours, 12 hours, 24 hours, 48 ​​hours, or 96 hours.

[0028] Further, in step S2, the amino-containing silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminoethylaminomethyltriethoxysilane, aminoethylaminopropyltrimethoxysilane, aminoethylaminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, aminohexylaminomethyltrimethoxysilane, methylaminopropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, aminoethylaminopropylmethyldimethoxysilane, diethylenetriaminopropylmethyldimethoxysilane, methylaminopropylmethyldiethoxysilane and methylaminomethylmethyldiethoxysilane.

[0029] Preferably, the amino-containing silane coupling agent is 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminoethylaminomethyltriethoxysilane, aminoethylaminopropyltrimethoxysilane, aminoethylaminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, and aminohexylaminomethyltrimethoxysilane.

[0030] Preferably, in step S2, the solvent used in the amino-containing silane coupling agent solution is selected from one or more of water, methanol, ethanol, isopropanol, ethylene glycol, 1,4-butanediol, 1,2,4-butanetriol, 1,6-hexanediol, pentanediol, glycerol, toluene, acetonitrile, acetone, methyl acetate, and ethyl acetate.

[0031] Preferably, in step S2, the specific operation of the grafting modification is a stirring reaction.

[0032] Preferably, in step S2, the temperature of the grafting modification is 25-150° C. Preferably, the temperature of the grafting modification is 30-80° C., specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C.

[0033] Preferably, in step S2, the grafting modification time is 0.5 to 48 hours, preferably, the grafting modification time is 2 to 24 hours, specifically 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, 12 hours, 18 hours, or 24 hours.

[0034] Preferably, in step S2, the volume percentage of the silane coupling agent in the amino-containing silane coupling agent solution is 0.01-30%, preferably 0.1-10%, specifically 0.1%, 0.2%, 0.5%, 1%, 2%, 3%, 5%, 10%.

[0035] Preferably, in step S3, the fullerene is selected from C 20 , C 60 , C 70 , C 72 , C 76 , C 80 , C 84 , C 96 Preferably, the fullerene is C 60 , C 70 , C 76 , C 80 , C 84 .

[0036] Preferably, in step S3, the fullerene-containing solvent is selected from one or more of the aromatic solvents toluene, chlorobenzene, 1,2-dichlorobenzene, m-xylene, or the non-aromatic solvents carbon disulfide and carbon tetrachloride.

[0037] Preferably, the specific operation of fullerene modification is a stirring reaction.

[0038] Preferably, in step S3, the temperature of the fullerene modification is 20-150° C. Preferably, the temperature of the fullerene modification is 40-120° C., specifically 40° C., 50° C., 60° C., 80° C., 100° C., 120° C.

[0039] Preferably, in step S3, the fullerene modification time is 1 to 240 hours. Preferably, the fullerene modification time is 6 to 120 hours, specifically 6 hours, 12 hours, 24 hours, 48 ​​hours, 72 hours, 96 hours, 120 hours.

[0040] Preferably, in step S3, the molar concentration of the fullerene in the solvent is 0.1-100 mmol / L, preferably 1.0-50 mmol / L, specifically 1.0 mmol / L, 5.0 mmol / L, 10 mmol / L, 20 mmol / L, 50 mmol / L.

[0041] At the same time, the present invention also protects the fullerene-modified transition metal hydroxide nano-array material prepared by the preparation method.

[0042] Furthermore, the present invention protects the application of the fullerene-modified transition metal hydroxide nanoarray material in organic electro-oxidation reactions.

[0043] Preferably, the organic electro-oxidation is an organic electro-oxidation reaction of organic alcohols, aldehydes, ketones, amines, etc.

[0044] The fullerene-modified transition metal hydroxide nano-array material prepared by the invention has excellent catalytic activity, can catalyze organic electro-oxidation reaction, and improve its Faraday efficiency.

[0045] The present invention has the following beneficial effects:

[0046] The present invention grafts transition metal hydroxide nanoarrays with silane coupling agents having amino groups so that the material surface has amino groups, and finally obtains transition metal hydroxide nanoarray materials with surface fullerene modified by addition reaction of surface amino groups with fullerene carbon-carbon double bonds. The preparation method of the present invention is economical, simple, rapid, and can achieve large-scale mass production. At the same time, the material prepared by the present invention benefits from the modification of fullerenes, so that its surface electronic structure is optimized and the catalytic activity is further improved; at the same time, the modification of fullerenes is conducive to the adsorption and enrichment of organic substrates on the surface of the catalytic material, thereby improving the mass transfer efficiency. Based on the above-mentioned improvement mechanism, the obtained transition metal hydroxide nanoarray material with surface fullerene modified exhibits excellent electrocatalytic performance for a series of organic electro-oxidation reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 TM / Ni(OH) prepared in Example 1 2 -C 84 SEM image of nanoarray material.

[0048] Figure 2 The NF / CoCe-OH-C prepared in Example 2 60 SEM image of nanoarray material.

[0049] Figure 3 IF / CuY-OH-C prepared in Example 3 76 SEM image of nanoarray material.

[0050] Figure 4 The SS / FeMnCr-OH-C prepared in Example 4 80 SEM image of nanoarray material.

[0051] Figure 5 CC / NiZnV-OH-C prepared in Example 5 70 SEM image of nanoarray material.

[0052] Figure 6 The AlF / NiCoSc-OH-C prepared in Example 6 60 SEM image of nanoarray material.

[0053] Figure 7 These are LSV diagrams of the electrocatalytic cyclohexanol oxidation reaction of the nanoarray materials of Example 1 and Comparative Examples 1, 2, and 3.

[0054] Figure 8 LSV diagrams of the electrocatalytic ethylene glycol oxidation reaction of the nanoarray materials of Example 2 and Comparative Example 4.

[0055] Fig. 9 LSV diagrams of the electrocatalytic oxidation reaction of benzylamine by the nanoarray materials of Example 3 and Comparative Example 5.

[0056] Fig.10 LSV diagrams of the electrocatalytic oxidation reaction of 5-hydroxymethylfurfural by the nanoarray materials of Example 4 and Comparative Example 6.

[0057] Fig.11 2. LSV diagrams of the electrocatalytic oxidation reaction of benzyl alcohol by the nanoarray materials of Example 5 and Comparative Example 7.

[0058] Fig.12 LSV diagrams of the electrocatalytic cyclohexanone oxidation reaction of the nanoarray materials of Example 6 and Comparative Example 8. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0060] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0061] Example 1TM / Ni(OH) 2 -C 84 Nanoarray Materials

[0062] The TM / Ni(OH) 2 -C 84 The method for preparing the nanoarray material comprises the following steps:

[0063] S1. 1.244 g (5 mmol) of nickel acetate tetrahydrate (NiC 4 H 6 O 4 ·4H 2 O) and 2.804 g (20 mmol) hexamethylenetetramine (HMTA) were dissolved in 50 mL ultrapure water, stirred on a stirrer for 1 h (the stirrer speed was 500 rpm) until a uniform mixed solution was obtained, then immersed in 2 pieces of 2×4 cm pretreated titanium mesh (TM), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 120 ° C for 12 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60 ° C for 12 h to obtain Ni(OH) loaded on the TM current collector. 2 Nanoarray materials;

[0064] S2. Load Ni(OH) 2 The nanoarray material was immersed in 2% 3-aminopropyltriethoxysilane (C 9 H 23 NO 3 Si) solution, stirred at 30 °C for 24 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 6 h to obtain Ni(OH) 2 @C 9 H 23 NO 3 Si nanoarray materials;

[0065] S3. Loading Ni(OH) on the TM current collector obtained in step S2 2 @C 9 H 23 NO 3The Si nanoarray material was immersed in 1mmol / LC 84 The solution was stirred at 80 °C for 48 h, then rinsed with ultrapure water and anhydrous ethanol three times, and dried in a forced air drying oven at 60 °C for 12 h to obtain Ni(OH) 2 -C 84 Nanoarray materials.

[0066] Material Characterization:

[0067] The obtained product was characterized by SEM material morphology. Figure 1 , it can be seen from the figure that the nanosheet structure is evenly distributed on the TM current collector.

[0068] Example 2NF / CoCe-OH-C 60 Nanoarray Materials

[0069] The NF / CoCe-OH-C 60 The method for preparing the nanoarray material comprises the following steps:

[0070] S1. 43.655 g (150 mmol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O), 65.133 g (150 mmol) of cerium nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O) and 144.144 g (2.4 mol) urea (CH 4 N 2 O) was dissolved in 100 mL of ultrapure water, stirred on a stirrer for 3 h (the stirrer speed was 650 rpm) until a uniform mixed solution was obtained, then immersed in 3 pieces of 4×5 cm pretreated nickel foam (NF), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvent thermal reaction, reacted at 180° C. for 8 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a blast drying oven at 60° C. for 24 h to obtain the CoCe-OH nanoarray material loaded on the NF current collector;

[0071] S2. The CoCe-OH nanoarray material loaded with the NF current collector obtained in step S1 is immersed in 0.5% aminoethylaminomethyltriethoxysilane (C 9 H 24 N 2 O 3 Si) solution, stirred at 60 °C for 8 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 12 h to obtain CoCe-OH@C loaded on the NF current collector.9 H 24 N 2 O 3 Si nanoarray materials;

[0072] S3. Load the CoCe-OH@C on the NF current collector obtained in step S2 9 H 24 N 2 O 3 The Si nanoarray material was immersed in 10 mmol / LC 60 The solution was stirred at 100 °C for 24 h, then rinsed with ultrapure water and anhydrous ethanol three times, and dried in a forced air drying oven at 60 °C for 24 h to obtain the CoCe-OH-C supported on the NF current collector. 60 Nanoarray materials.

[0073] Material Characterization:

[0074] The obtained product was characterized by SEM material morphology. Figure 2 , it can be seen from the figure that the nanosheet structure is evenly distributed on the NF current collector.

[0075] Example 3IF / CuY-OH-C 76 Nanoarray Materials

[0076] IF / CuY-OH-C 76 The method for preparing the nanoarray material comprises the following steps:

[0077] S1. 3.3414 g (19.6 mmol) of copper chloride dihydrate (CuCl 2 ·2H 2 O), 0.1213 g (0.4 mmol) yttrium chloride hexahydrate (YCl 3 6H 2 O) and 1.402 g (20 mmol) of aqueous ammonia (NH 3 ·H 2 O) (25%-28% wt) was dissolved in 40 mL of ultrapure water, and stirred on a stirrer for 0.5 h (the stirrer speed was 500 rpm) to obtain a uniform mixed solution, then immersed in 2 pieces of 2×3 cm pretreated foamed iron (IF), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvent thermal reaction, reacted at 200° C. for 1 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a blast drying oven at 60° C. for 12 h, to obtain a CuY-OH nanoarray material loaded on the IF current collector;

[0078] S2. The CuY-OH nanoarray material loaded with the IF current collector obtained in step S1 is immersed in 10% aminohexylaminomethyltrimethoxysilane (C 10 H 26 N 2 O 3 Si) solution, stirred at 80 °C for 2 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 12 h to obtain CuY-OH@C loaded on the IF current collector. 10 H 26 N 2 O 3 Si nanoarray materials;

[0079] S3. The CuY-OH@C loaded on the IF current collector obtained in step S2 10 H 26 N 2 O 3 The Si nanoarray material was immersed in 1mmol / LC 76 The solution was stirred at 60 °C for 72 h, then rinsed with ultrapure water and anhydrous ethanol for 3 times, and dried in a forced air drying oven at 60 °C for 12 h to obtain the CuY-OH-C supported on the IF current collector. 76 Nanoarray materials.

[0080] Material Characterization:

[0081] The obtained product was characterized by SEM material morphology. Figure 3 , it can be seen from the figure that the nanosheet structure is evenly distributed on the IF current collector.

[0082] Example 4SS / FeMnCr-OH-C 80 Nanoarray Materials

[0083] The SS / FeMnCr-OH-C 80 The method for preparing the nanoarray material comprises the following steps:

[0084] S1. 4.866 g (18 mmol) of ferric chloride hexahydrate (FeCl 3 6H 2 O), 0.198 g (1 mmol) manganese chloride tetrahydrate (MnCl 2 ·4H 2 O), 0.266 g (1 mmol) chromium chloride hexahydrate (CrCl 3 6H 2O) and 2.804g (20mmol) hexamethylenetetramine (HMTA) were dissolved in 20mL ultrapure water, stirred on a stirrer for 2h (the stirrer speed was 600rpm) until a uniform mixed solution was obtained, then immersed in 2 pieces of 1×3cm pretreated stainless steel (SS), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvothermal reaction, reacted at 100°C for 48h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a blast drying oven at 60°C for 6h to obtain the FeMnCr-OH nanoarray material loaded on the SS current collector;

[0085] S2. The FeMnCr-OH nanoarray material loaded with the SS current collector obtained in step S1 is immersed in 1% diethylenetriaminepropyltrimethoxysilane (C 10 H 27 N 3 O 3 Si) solution, stirred at 40 °C for 18 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 6 h to obtain FeMnCr-OH@C loaded on the SS current collector. 10 H 27 N 3 O 3 Si nanoarray materials;

[0086] S3. Load the FeMnCr-OH@C 10 H 27 N 3 O 3 The Si nanoarray material was immersed in 20 mmol / LC carbon disulfide as solvent. 80 The solution was stirred at 40 °C for 120 h, then rinsed with ultrapure water and anhydrous ethanol for 3 times, and dried in a forced air drying oven at 60 °C for 12 h to obtain the FeMnCr-OH-C supported on the SS current collector. 80 Nanoarray materials.

[0087] Material Characterization:

[0088] The obtained product was characterized by SEM material morphology. Figure 4 , it can be seen from the figure that the nanosheet structure is evenly distributed on the SS current collector.

[0089] Example 5CC / NiZnV-OH-C 70 Nanoarray Materials

[0090] The CC / NiZnV-OH-C 70 The method for preparing the nanoarray material comprises the following steps:

[0091] S1. 15.166 g (98 mmol) of nickel sulfate (NiSO 4 )、0.179 g (1 mmol) zinc sulfate (ZnSO 4 ·H 2 O), 0.163 g (1 mmol) vanadyl sulfate hydrate (VOSO 4 ·xH 2 O) and 48.048 g (800 mmol) urea (CH 4 N 2 O) was dissolved in 1000 mL of ultrapure water, stirred on a stirrer for 4 h (the stirrer speed was 550 rpm) to obtain a uniform mixed solution, then immersed in 4 pieces of 5×6 cm pretreated carbon cloth (CC), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvent thermal reaction, reacted at 150° C. for 24 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a blast drying oven at 60° C. for 24 h to obtain the NiZnV-OH nanoarray material loaded on the CC current collector;

[0092] S2. The NiZnV-OH nanoarray material loaded with CC current collector obtained in step S1 is immersed in 0.1% methylaminopropyltrimethoxysilane (C 7 H 19 NO 3 Si) solution, stirred at 70 °C for 4 h, rinsed with anhydrous ethanol 3 times after grafting modification, and dried in a forced air drying oven at 60 °C for 12 h to obtain NiZnV-OH@C loaded on the CC current collector. 7 H 19 NO 3 Si nanoarray materials;

[0093] S3. Load NiZnV-OH@C on the CC current collector obtained in step S2 7 H 19 NO 3 The Si nanoarray material was immersed in 50 mmol / LC 70 The solution was stirred at 120 °C for 6 h, then rinsed with ultrapure water and anhydrous ethanol for 3 times, and dried in a forced air drying oven at 60 °C for 24 h to obtain the NiZnV-OH-C supported on the CC current collector. 70 Nanoarray materials.

[0094] Material Characterization:

[0095] The obtained product was characterized by SEM material morphology. Figure 5 , it can be seen from the figure that the nanosheet structure is evenly distributed on the CC current collector.

[0096] Example 6AlF / NiCoSc-OH-C 60 Nanoarray Materials

[0097] The AlF / NiCoSc-OH-C 60 The method for preparing the nanoarray material comprises the following steps:

[0098] S1. 0.093 g (0.32 mmol) of nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O), 0.012 g (0.04 mmol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O), 0.014 g (0.04 mmol) scandium nitrate hexahydrate (Sc(NO 3 ) 3 6H 2 O) and 0.359g (6.4mmol) potassium hydroxide (KOH) were dissolved in 40mL ultrapure water, stirred on a stirrer for 1h (the stirrer speed was 450rpm) until a uniform mixed solution was obtained, then immersed in 2 pieces of 1×3cm pretreated aluminum foil (AlF), transferred to a high-pressure reactor, sealed and placed in a blast drying oven for solvothermal reaction, reacted at 60°C for 96h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a blast drying oven at 60°C for 12h to obtain a NiCoSc-OH nanoarray material supported on the AlF current collector;

[0099] S2. The NiCoSc-OH nanoarray material loaded on the AlF current collector obtained in step S1 is immersed in 0.2% aminoethylaminopropyltrimethoxysilane (C 8 H 22 N 2 O 3 Si) solution, stirred at 50 °C for 10 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 6 h to obtain NiCoSc-OH@C supported on the AlF current collector. 8 H 22 N 2 O 3 Si nanoarray materials;

[0100] S3. NiCoSc-OH@C loaded on the AlF current collector obtained in step S2 8 H 22 N 2 O 3 The Si nanoarray material was immersed in 5mmol / LC60 The solution was stirred at 50 °C for 96 h, then rinsed with ultrapure water and anhydrous ethanol for 3 times, and dried in a forced air drying oven at 60 °C for 12 h to obtain NiCoSc-OH-C supported on the AlF current collector. 60 Nanoarray materials.

[0101] Material Characterization:

[0102] The obtained product was characterized by SEM material morphology. Figure 6 , it can be seen from the figure that the nanosheet structure is evenly distributed on the AlF current collector.

[0103] Comparative Example 1TM / Ni(OH) 2 Nanoarray Materials

[0104] The TM / Ni(OH) 2 The method for preparing the nanoarray material comprises the following steps:

[0105] S1. 1.244 g (5 mmol) of nickel acetate tetrahydrate (NiC 4 H 6 O 4 ·4H 2 O) and 2.804 g (20 mmol) hexamethylenetetramine (HMTA) were dissolved in 50 mL ultrapure water, stirred on a stirrer for 1 h (the stirrer speed was 500 rpm) until a uniform mixed solution was obtained, then immersed in 2 pieces of 2×4 cm pretreated titanium mesh (TM), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 120 ° C for 12 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60 ° C for 12 h to obtain Ni(OH) loaded on the TM current collector. 2 Nanoarray materials.

[0106] Compared with Example 1, the difference of Comparative Example 1 is that 3-aminopropyltriethoxysilane (C 9 H 23 NO 3 Si) grafting and subsequent fullerene C 84 Modification.

[0107] Comparative Example 2TM / Ni(OH) 2 -Carbon nanoarray material

[0108] The TM / Ni(OH) 2 -The preparation method of the carbon nanoarray material comprises the following steps:

[0109] S1. 1.244 g (5 mmol) of nickel acetate tetrahydrate (NiC4 H 6 O 4 ·4H 2 O) and 2.804 g (20 mmol) hexamethylenetetramine (HMTA) were dissolved in 50 mL ultrapure water, stirred on a stirrer for 1 h (the stirrer speed was 500 rpm) until a uniform mixed solution was obtained, then immersed in 2 pieces of 2×4 cm pretreated titanium mesh (TM), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 120 ° C for 12 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60 ° C for 12 h to obtain Ni(OH) loaded on the TM current collector. 2 Nanoarray materials;

[0110] S2. Load Ni(OH) 2 The nanoarray material was immersed in 2% 3-aminopropyltriethoxysilane (C 9 H 23 NO 3 Si) solution, stirred at 30 °C for 24 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 6 h to obtain Ni(OH) 2 @C 9 H 23 NO 3 Si nanoarray materials;

[0111] S3. Loading Ni(OH) on the TM current collector obtained in step S2 2 @C 9 H 23 NO 3 The Si nanoarray material is immersed in a toluene solution dispersed with 1.009 g / L carbon black (the mass concentration of carbon black in the solution is the same as that in the toluene solution in step S3 of Example 1). 84 The mixture was stirred at 80 °C for 48 h, then rinsed with ultrapure water and anhydrous ethanol for 3 times, and dried in a forced air drying oven at 60 °C for 12 h to obtain Ni(OH) loaded on the TM current collector. 2 -Carbon nanoarray material.

[0112] Compared with Example 1, the difference of Comparative Example 2 is that no fullerene C 84 Instead of surface modification, carbon black modification is performed.

[0113] Comparative Example 3TM / Ni(OH) 2 -Graphene nanoarray material

[0114] The TM / Ni(OH) 2 -The preparation method of graphene nanoarray material comprises the following steps:

[0115] S1. 1.244 g (5 mmol) of nickel acetate tetrahydrate (NiC 4 H 6 O 4 ·4H 2 O) and 2.804 g (20 mmol) hexamethylenetetramine (HMTA) were dissolved in 50 mL ultrapure water, stirred on a stirrer for 1 h (the stirrer speed was 500 rpm) until a uniform mixed solution was obtained, then immersed in 2 pieces of 2×4 cm pretreated titanium mesh (TM), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 120 ° C for 12 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60 ° C for 12 h to obtain Ni(OH) loaded on the TM current collector. 2 Nanoarray materials;

[0116] S2. Load Ni(OH) 2 The nanoarray material was immersed in 2% 3-aminopropyltriethoxysilane (C 9 H 23 NO 3 Si) solution, stirred at 30 °C for 24 h, rinsed with anhydrous ethanol three times after grafting modification, and dried in a forced air drying oven at 60 °C for 6 h to obtain Ni(OH) 2 @C 9 H 23 NO 3 Si nanoarray materials;

[0117] S3. Loading Ni(OH) on the TM current collector obtained in step S2 2 @C 9 H 23 NO 3 The Si nanoarray material is immersed in a toluene solution dispersed with 1.009 g / L graphene (the mass concentration of graphene in the solution is the same as that in the toluene solution in step S3 of Example 1). 84 The mixture was stirred at 80 °C for 48 h, then rinsed with ultrapure water and anhydrous ethanol for 3 times, and dried in a forced air drying oven at 60 °C for 12 h to obtain Ni(OH) loaded on the TM current collector. 2 -Graphene nanoarray material.

[0118] Compared with Example 1, the difference of Comparative Example 3 is that no fullerene C 84Instead of surface modification, graphene is modified.

[0119] Comparative Example 4NF / CoCe-OH Nanoarray Material

[0120] The preparation method of the NF / CoCe-OH nanoarray material comprises the following steps:

[0121] S1. 43.655 g (150 mmol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O), 65.133 g (150 mmol) of cerium nitrate hexahydrate (Ce(NO 3 ) 3 6H 2 O) and 144.144 g (2.4 mol) urea (CH 4 N 2 O) was dissolved in 100 mL of ultrapure water, stirred on a stirrer for 3 h (the stirrer speed was 650 rpm) to obtain a uniform mixed solution, then immersed in 3 pieces of 4×5 cm pretreated nickel foam (NF), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvothermal reaction at 180 ° C for 8 h. After the reaction was completed, it was allowed to cool naturally. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60 ° C for 24 h to obtain the CoCe-OH nanoarray material loaded on the NF current collector.

[0122] Compared with Example 2, the difference of Comparative Example 4 is that aminoethylaminomethyltriethoxysilane (C 9 H 24 N 2 O 3 Si) grafting and subsequent fullerene C 60 Modification.

[0123] Comparative Example 5 IF / CuY-OH Nanoarray Material

[0124] The preparation method of the IF / CuY-OH nanoarray material comprises the following steps:

[0125] S1. 3.3414 g (19.6 mmol) of copper chloride dihydrate (CuCl 2 ·2H 2 O), 0.1213 g (0.4 mmol) yttrium chloride hexahydrate (YCl 3 6H 2 O) and 1.402 g (20 mmol) of aqueous ammonia (NH 3 ·H 2O) (25%-28% wt) was dissolved in 40 mL of ultrapure water, and stirred on a stirrer for 0.5 h (the stirrer speed was 500 rpm) to obtain a uniform mixed solution, then immersed in 2 pieces of 2×3 cm pretreated foamed iron (IF), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvent thermal reaction, reacted at 200° C. for 1 h, and allowed to cool naturally after the reaction was completed. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60° C. for 12 h to obtain the CuY-OH nanoarray material loaded on the IF current collector.

[0126] Compared with Example 3, the difference of Comparative Example 5 is that aminohexylaminomethyltrimethoxysilane (C 10 H 26 N 2 O 3 Si) grafting and subsequent fullerene C 76 Modification.

[0127] Comparative Example 6SS / FeMnCr-OH Nanoarray Material

[0128] The preparation method of the SS / FeMnCr-OH nanoarray material comprises the following steps:

[0129] S1. 4.866 g (18 mmol) of ferric chloride hexahydrate (FeCl 3 6H 2 O), 0.198 g (1 mmol) manganese chloride tetrahydrate (MnCl 2 ·4H 2 O), 0.266 g (1 mmol) chromium chloride hexahydrate (CrCl 3 6H 2 O) and 2.804g (20mmol) hexamethylenetetramine (HMTA) were dissolved in 20mL ultrapure water, stirred on a stirrer for 2h (the stirrer speed was 600rpm) to obtain a uniform mixed solution, then immersed in 2 pieces of 1×3cm pretreated stainless steel (SS), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvothermal reaction, reacted at 100°C for 48h, and allowed to cool naturally after the reaction. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60°C for 6h to obtain the FeMnCr-OH nanoarray material loaded on the SS current collector.

[0130] Compared with Example 4, the difference of Comparative Example 6 is that diethylenetriaminepropyltrimethoxysilane (C 10 H 27 N 3 O 3 Si) grafting and subsequent fullerene C80 Modification.

[0131] Comparative Example 7CC / NiZnV-OH Nanoarray Material

[0132] The preparation method of the CC / NiZnV-OH nanoarray material comprises the following steps:

[0133] S1. 15.166 g (98 mmol) of nickel sulfate (NiSO 4 )、0.179 g (1 mmol) zinc sulfate (ZnSO 4 ·H 2 O), 0.163 g (1 mmol) vanadyl sulfate hydrate (VOSO 4 ·xH 2 O) and 48.048 g (800 mmol) urea (CH 4 N 2 O) was dissolved in 1000 mL of ultrapure water, stirred on a stirrer for 4 h (the stirrer speed was 550 rpm) to obtain a uniform mixed solution, then immersed in 4 pieces of 5×6 cm pretreated carbon cloth (CC), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvothermal reaction at 150°C for 24 h. After the reaction was completed, it was allowed to cool naturally. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60°C for 24 h to obtain the NiZnV-OH nanoarray material loaded on the CC current collector.

[0134] Compared with Example 5, the difference of Comparative Example 7 is that methylaminopropyltrimethoxysilane (C 7 H 19 NO 3 Si) grafting and subsequent fullerene C 70 Modification.

[0135] Comparative Example 8 AlF / NiCoSc-OH Nanoarray Material

[0136] The preparation method of the AlF / NiCoSc-OH nanoarray material comprises the following steps:

[0137] S1. 0.093 g (0.32 mmol) of nickel nitrate hexahydrate (Ni(NO 3 ) 2 6H 2 O), 0.012 g (0.04 mmol) of cobalt nitrate hexahydrate (Co(NO 3 ) 2 6H 2 O), 0.014 g (0.04 mmol) scandium nitrate hexahydrate (Sc(NO 3 )3 6H 2 O) and 0.359g (6.4mmol) potassium hydroxide (KOH) were dissolved in 40mL ultrapure water, stirred on a stirrer for 1h (the stirrer speed was 450rpm) to obtain a uniform mixed solution, then immersed in 2 pieces of 1×3cm pretreated aluminum foil (AlF), transferred to a high-pressure reactor, sealed and placed in a forced air drying oven for solvothermal reaction, reacted at 60°C for 96h, and allowed to cool naturally after the reaction. The cooled material was washed with ultrapure water and anhydrous ethanol for 3 times respectively, and dried in a forced air drying oven at 60°C for 12h to obtain the NiCoSc-OH nanoarray material supported on the AlF current collector.

[0138] Compared with Example 6, the difference of Comparative Example 8 is that aminoethylaminopropyltrimethoxysilane (C 8 H 22 N 2 O 3 Si) grafting and subsequent fullerene C 60 Modification.

[0139] Application Example 1 Performance Test of Cyclohexanol Electrooxidation (CXLOR)

[0140] The electrochemical test was performed using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N) and a standard three-electrode system; the main indicators for evaluating the activity of the nanoarray materials prepared in the embodiments or comparative examples were: the voltage (E) required to achieve the same current density, the generation rate of the target product, and the Faraday efficiency.

[0141] Three-electrode system: the nanoarray material prepared in the embodiment or comparative example is used as the working electrode (1×1 cm), the Pt sheet (2×2 cm) is used as the counter electrode, the Hg / HgO electrode (immersed in 1.0 M KOH solution) is used as the reference electrode, and the electrolyte used is a potassium hydroxide solution containing cyclohexanol (1 M KOH + 0.1 M cyclohexanol).

[0142] Before each electrochemical data acquisition, the solution resistance (R s) values, the CV curves were scanned multiple times in the voltage range of 0.1-0.9V vs.Hg / HgO until they were stable, and then the LSV test was performed in the voltage range of 0-1.0V vs.Hg / HgO, and the LSV curve was compensated for 95% IR, and the potential value E(Hg / HgO) was converted to E(RHE) according to the formula E(RHE)=E(Hg / HgO)+0.0977+0.05916×pH. In addition, the CXLOR performance of the material was tested for 5h by chronoamperometry (CA test), and the electrolyte after the CA test was quantitatively analyzed by GC. Specific test process: After the CA test is completed, 2mL of electrolyte is drawn with a syringe and injected into a certain amount of deionized water for dilution, and then a small amount of 1M HCl is added to adjust the pH value of the solution, and then dichloromethane is added for extraction, the organic phase is transferred to a sample bottle, and a small amount of Na 2 SO 4 For dehydration, take 2 μL of sample and inject it into the injector. GC test parameters: detector is FID detector, chromatographic column is DB-5ms capillary column, carrier gas is N 2 The injection port temperature was 250°C, the FID detector temperature was 300°C, and the H 2 Flow rate 30mL / min, air flow rate 400mL / min, tail blow N 2 The flow rate was 25 mL / min. GC-MS was used for subsequent qualitative analysis.

[0143] This application example is for Example 1 (TM / Ni(OH) 2 -C 84 ) and Comparative Example 1 (TM / Ni(OH) 2 ), Comparative Example 2 (TM / Ni(OH) 2 -Carbon), Comparative Example 3 (TM / Ni(OH) 2 -Graphene) was tested for its CXLOR performance, and the LSV results are shown in Figure 7 .Depend on Figure 7 It can be seen that for CXLOR performance, TM / Ni(OH) 2 -C 84 With TM / Ni(OH) 2 、TM / Ni(OH) 2 -Carbon、TM / Ni(OH) 2 -Graphene, achieving the same current density of 50 mA cm -2 When the electric potential (E 50 ) is smaller, E 50 vs.RHE respectively TM / Ni(OH) 2 -C 84 (1.422V) <TM / Ni(OH)2 -Graphene (1.571V) <TM / Ni(OH) 2 -Carbon (1.588V) <TM / Ni(OH) 2 (1.611 V), which preliminarily indicates that the nanoarray material prepared in the embodiment of the present invention has better CXLOR performance.

[0144] According to GC test, Example 1 (TM / Ni(OH) 2 -C 84 ) The generation rate of adipic acid at 1.45 V vs. RHE is 0.079 mmol / (h·cm 2 ), the Faraday efficiency is 91.2%; Comparative Example 1 (TM / Ni(OH) 2 ) The generation rate of adipic acid at 1.45 V vs. RHE is 0.032 mmol / (h·cm 2 ), the Faraday efficiency is 48.6%; Comparative Example 2 (TM / Ni(OH) 2 -Carbon) at 1.45V vs.RHE, the generation rate of adipic acid is 0.046mmol / (h·cm 2 ), the Faraday efficiency is 52.8%; Comparative Example 3 (TM / Ni(OH) 2 -Graphene) at 1.45V vs. RHE with a rate of adipic acid generation of 0.055mmol / (h·cm 2 ), the Faraday efficiency is 59.4%. According to the above performance results, it can be seen that Example 1 (TM / Ni(OH) 2 -C 84 ) has better CXLOR performance than comparative example 1 (TM / Ni(OH) 2 ), Comparative Example 2 (TM / Ni(OH) 2 -Carbon) and Comparative Example 3 (TM / Ni(OH) 2 -Graphene). The above experimental results show that only the nanoarray material modified with fullerene has a good catalytic organic electro-oxidation effect, and its Faraday efficiency is increased by 72.72% compared with the nanoarray material modified with carbon black (Comparative Example 2), and by 53.54% compared with the nanoarray material modified with graphene (Comparative Example 3).

[0145] Application Example 2 Performance Test of Ethylene Glycol Electrooxidation (EGOR)

[0146] The electrochemical test was performed using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N) and a standard three-electrode system; the main indicators for evaluating the activity of the nanoarray materials prepared in the embodiments or comparative examples were: the voltage (E) required to achieve the same current density, the generation rate of the target product, and the Faraday efficiency.

[0147] Three-electrode system: The nanoarray material prepared in the embodiment or comparative example is used as the working electrode (1×1 cm), the graphite rod is used as the counter electrode, the Hg / HgO electrode (immersed in 1.0 M KOH solution) is used as the reference electrode, and the electrolyte used is a potassium hydroxide solution containing ethylene glycol (1 M KOH + 0.1 M ethylene glycol).

[0148] Before each electrochemical data acquisition, the solution resistance (R s ) values, the CV curves were scanned multiple times in the voltage range of 0.1~0.9V vs.Hg / HgO until they were stable, and then the LSV test was carried out in the voltage range of 0.1~0.9V vs.Hg / HgO, and the LSV curve was compensated for 95% IR, and the potential value E(Hg / HgO) was converted to E(RHE) according to the formula E(RHE)=E(Hg / HgO)+0.0977+0.05916×pH. In addition, the EGOR performance of the material was tested for 3h by chronoamperometry (CA test), and the electrolyte after the CA test was quantitatively analyzed by HPLC. Specific test process: After the CA test is completed, 200μL of electrolyte is drawn out with a syringe and injected into a certain amount of deionized water for dilution, and then a small amount of 0.5MH 2 SO 4 Adjust the pH value of the solution, filter the solution through a 0.22 μm filter membrane, and take 20 μL of the sample and inject it into the injector. HPLC test parameters: the detector is a UV detector, the chromatographic column is an organic acid column, and the mobile phase is 8 mM H 2 SO 4 , wavelength of 210nm, column temperature of 50℃, flow rate of 0.6mL / min, detection time of 16min. HPLC-MS was used for qualitative analysis.

[0149] This application example is for Example 2 (NF / CoCe-OH-C 60 ) and comparative example 4 (NF / CoCe-OH) were tested for EGOR performance, and the LSV results are shown in Figure 8 As can be seen from the figure, for EGOR performance, NF / CoCe-OH-C 60 Compared with NF / CoCe-OH, the same current density of 100 mA cm -2 When the electric potential (E 100 ) is smaller, E100 vs. RHE are NF / CoCe-OH-C 60 (1.406 V) < NF / CoCe-OH(1.452 V), preliminarily indicating that the nanoarray material prepared in the embodiment of the present invention has better EGOR performance.

[0150] According to HPLC tests, Example 2 (NF / CoCe-OH-C 60 ) has a formic acid production rate of 0.816 mmol / (h·cm 2 ) at 1.45 V vs. RHE, and a Faraday efficiency of 95.1%; Comparative Example 4 (NF / CoCe-OH) has a formic acid production rate of 0.563 mmol / (h·cm 2 ) at 1.45 V vs. RHE, and a Faraday efficiency of 61.2%. According to the above performance results, it can be seen that the EGOR performance of Example 2 (NF / CoCe-OH-C 60 ) is better than that of Comparative Example 4 (NF / CoCe-OH).

[0151] Performance test of the electro-oxidation reaction of benzylamine (BANOR) in Application Example 3

[0152] Electrochemical tests were carried out using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N), and a standard three-electrode system was used for measurement; the main indicators for evaluating the activity of the nanoarray materials prepared in the examples or comparative examples are: the voltage (E) required to reach the same current density, the production rate of the target product, and the Faraday efficiency.

[0153] Three-electrode system: The nanoarray material prepared in the example or comparative example was used as the working electrode (1×1 cm), a Pt sheet (2×2 cm) was used as the counter electrode, and a Hg / HgO electrode (immersed in 1.0 M KOH solution) was used as the reference electrode. The electrolyte used was a potassium hydroxide solution containing benzylamine (1 M KOH + 0.01 M benzylamine).

[0154] Before each electrochemical data collection, the solution resistance (R) of all materials was collected at the open-circuit potential s) Values were scanned multiple times for CV curves until stable within the voltage range of 0.2 - 0.8 V vs. Hg / HgO, and then LSV tests were conducted within the voltage range of 0.1 - 1.0 V vs. Hg / HgO. The LSV curve was compensated by 95% IR. Meanwhile, according to the formula E(RHE) = E(Hg / HgO) + 0.0977 + 0.05916 × pH, the potential value E(Hg / HgO) was converted to E(RHE). In addition, the BANOR performance of the material was tested for 2 h by chronoamperometry (CA test), and the electrolyte after CA test was quantitatively analyzed by HPLC. Specific test procedure: After the CA test, 200 μL of the electrolyte was extracted with a syringe and injected into a certain amount of deionized water for dilution, and then a small amount of 0.5 M H 2 SO 4 was added to adjust the pH value of the solution. The solution was filtered through a 0.22 μm filter membrane, and then 20 μL of the sample was taken and injected into the injector. HPLC test parameters: The detector was a UV detector, the chromatographic column was C18, the mobile phase was a mixed solution of methanol and 0.05 M potassium dihydrogen phosphate (methanol: potassium dihydrogen phosphate = 70:30), the wavelength was 250 nm, the column temperature was 50 °C, the flow rate was 0.8 mL / min, and the detection time was 7 min. Subsequently, qualitative analysis was carried out by HPLC-MS.

[0155] This application example tested the BANOR performance of Example 3 (IF / CuY-OH-C 76 ) and Comparative Example 4 (IF / CuY-OH). The LSV results are shown in Fig. 9 . As can be seen from the figure, for the BANOR performance, when reaching the same current density of 10 mA·cm 76 , the potential (E -2 ) of IF / CuY-OH-C 10 is smaller than that of IF / CuY-OH. E 10 vs. RHE are 1.366 V for IF / CuY-OH-C 76 (1.366 V) < 1.406 V for IF / CuY-OH, preliminarily indicating that the nanorod array material prepared in the embodiment of the present invention has better BANOR performance.

[0156] According to the HPLC test, the production rate of benzonitrile for Example 3 (IF / CuY-OH-C 76 ) is 0.364 mmol / (h·cm 2 ) at 1.45 V vs. RHE, and the Faraday efficiency is 90.2%; the production rate of benzonitrile for Comparative Example 5 (IF / CuY-OH) is 0.242 mmol / (h·cm 2), the Faraday efficiency is 59.5%. According to the above performance results, it can be seen that Example 3 (IF / CuY-OH-C 76 ) has better BANOR performance than Comparative Example 5 (IF / CuY-OH).

[0157] Application Example 4 Performance Test of 5-Hydroxymethylfurfural Electrooxidation Reaction (HMFOR)

[0158] The electrochemical test was performed using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N) and a standard three-electrode system; the main indicators for evaluating the activity of the nanoarray materials prepared in the embodiments or comparative examples were: the voltage (E) required to achieve the same current density, the generation rate of the target product, and the Faraday efficiency.

[0159] Three-electrode system: the nanoarray material prepared in the embodiment or comparative example is used as the working electrode (1×1 cm), the Pt sheet (2×2 cm) is used as the counter electrode, the Hg / HgO electrode (immersed in 1.0 M KOH solution) is used as the reference electrode, and the electrolyte used is a potassium hydroxide solution containing 5-hydroxymethylfurfural (1 M KOH + 0.01 M 5-hydroxymethylfurfural).

[0160] Before each electrochemical data acquisition, the solution resistance (R s ) values, the CV curves were scanned multiple times in the voltage range of 0.2~0.8V vs.Hg / HgO until they were stable, and then the LSV test was carried out in the voltage range of 0.1~1.0V vs.Hg / HgO, and the LSV curve was compensated for 95% IR. At the same time, according to the formula E(RHE)=E(Hg / HgO)+0.0977+0.05916×pH, the potential value E(Hg / HgO) was converted to E(RHE). In addition, the HMFOR performance of the material was tested for 2h by chronoamperometry (CA test), and the electrolyte after the CA test was quantitatively analyzed by HPLC. Specific test process: After the CA test is completed, 200μL of electrolyte is drawn out with a syringe and injected into a certain amount of deionized water for dilution, and then a small amount of 0.5MH 2 SO 4 Adjust the pH value of the solution, filter the solution through a 0.22μm filter membrane, and take 20μL of the sample and inject it into the injector. HPLC test parameters: the detector is a UV detector, the chromatographic column is C18, the mobile phase is a mixed solution of methanol and 0.05M potassium dihydrogen phosphate (methanol: potassium dihydrogen phosphate = 70:30), the wavelength is 250nm, the column temperature is 50℃, the flow rate is 0.8mL / min, and the detection time is 7min. HPLC-MS is then used for qualitative analysis.

[0161] This application example tested the HMFOR performance of Example 4 (SS / FeMnCr-OH-C 80 ) and Comparative Example 6 (SS / FeMnCr-OH). The LSV results are shown in Fig.10 . As can be seen from the figure, for the HMFOR performance, SS / FeMnCr-OH-C 80 compared with SS / FeMnCr-OH, when reaching the same current density of 100 mA·cm -2 , the potential (E 100 ) is smaller. E 100 vs. RHE are SS / FeMnCr-OH-C 80 (1.400 V) < SS / FeMnCr-OH (1.468 V), preliminarily indicating that the nanoarray material prepared in the embodiment of the present invention has better HMFOR performance.

[0162] According to HPLC testing, for Example 4 (SS / FeMnCr-OH-C 80 ), the production rate of furandicarboxylic acid (FDCA) at 1.45 V vs. RHE is 0.157 mmol / (h·cm 2 ), and the Faraday efficiency is 94.8%; for Comparative Example 6 (SS / FeMnCr-OH), the production rate of furandicarboxylic acid (FDCA) at 1.45 V vs. RHE is 0.095 mmol / (h·cm 2 ), and the Faraday efficiency is 62.3%. According to the above performance results, it can be seen that the HMFOR performance of Example 4 (SS / FeMnCr-OH-C 80 ) is better than that of Comparative Example 6 (SS / FeMnCr-OH).

[0163] Performance test of electro-oxidation of benzyl alcohol (BAOR) in Application Example 5

[0164] The electrochemical test was carried out using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N), and a standard three-electrode system was used for measurement; the main indicators for evaluating the activity of the nanoarray materials prepared in the examples or comparative examples: the voltage (E) required to reach the same current density, the production rate of the target product, and the Faraday efficiency.

[0165] Three-electrode system: The nanoarray materials prepared in the examples or comparative examples were used as the working electrode (1×1 cm), a Pt sheet (2×2 cm) was used as the counter electrode, and a Hg / HgO electrode (immersed in 1.0 M KOH solution) was used as the reference electrode. The electrolyte used was a potassium hydroxide solution containing benzyl alcohol (1 M KOH + 0.01 M benzyl alcohol).

[0166] Before each electrochemical data acquisition, the solution resistance (R s ) values of all materials were collected at the open-circuit potential. The cyclic voltammetry (CV) curves were scanned multiple times within the voltage range of 0.1 - 0.9 V vs. Hg / HgO until stable, and then linear sweep voltammetry (LSV) tests were carried out within the voltage range of 0 - 1.0 V vs. Hg / HgO. The LSV curves were compensated by 95% IR. Meanwhile, according to the formula E(RHE) = E(Hg / HgO) + 0.0977 + 0.05916×pH, the potential value E(Hg / HgO) was converted to E(RHE). In addition, the BAOR performance of the materials was tested by chronoamperometry (CA test) for 1 h, and the electrolyte after CA test was quantitatively analyzed by HPLC. Specific test procedure: After the CA test was completed, 200 μL of the electrolyte was extracted with a syringe and injected into a certain amount of deionized water for dilution, and then a small amount of 0.5M H 2 SO 4 was added to adjust the pH value of the solution. The solution was filtered through a 0.22 μm filter membrane and 20 μL of the sample was injected into the injector. HPLC test parameters: The detector was a UV detector, the chromatographic column was C18, the mobile phase was a mixed solution of methanol and 0.05M potassium dihydrogen phosphate (methanol: potassium dihydrogen phosphate = 70:30), the wavelength was 250 nm, the column temperature was 50 °C, the flow rate was 0.8 mL / min, and the detection time was 7 min. Subsequently, qualitative analysis was carried out by HPLC-MS.

[0167] In this application example, the BAOR performance of Example 5 (CC / NiZnV-OH-C 70 ) and Comparative Example 7 (CC / NiZnV-OH) was tested. The LSV results are shown in Fig.11 . As can be seen from the figure, for the BAOR performance, compared with the CC / NiZnV-OH, the CC / NiZnV-OH-C 70 nanoarray material has a smaller E 200 , and E 200 vs. RHE are CC / NiZnV-OH-C 70 (1.556 V) < CC / NiZnV-OH (1.624 V), which preliminarily indicates that the nanoarray material prepared in the embodiment of the present invention has better BAOR performance.

[0168] According to the HPLC test, the formation rate of benzoic acid of Example 5 (SS / FeMnCr-OH-C 80 ) at 1.45 V vs. RHE was 0.562 mmol / (h·cm 2 ), and the Faraday efficiency was 90.7%; the formation rate of benzoic acid of Comparative Example 7 (CC / NiZnV-OH) at 1.45 V vs. RHE was 0.325 mmol / (h·cm2 ), the Faraday efficiency is 58.6%. According to the above performance results, it can be seen that Example 5 (CC / NiZnV-OH-C 70 ) has better HMFOR performance than Comparative Example 7 (CC / NiZnV-OH).

[0169] Application Example 6 Performance Test of Cyclohexanone Electrooxidation Reaction (CYCOR)

[0170] The electrochemical test was performed using a computer-controlled electrochemical workstation (Autolab, PGSTAT302N) and a standard three-electrode system; the main indicators for evaluating the activity of the nanoarray materials prepared in the embodiments or comparative examples were: the voltage (E) required to achieve the same current density, the generation rate of the target product, and the Faraday efficiency.

[0171] Three-electrode system: the nanoarray material prepared in the embodiment or comparative example is used as the working electrode (1×1 cm), the Pt sheet (2×2 cm) is used as the counter electrode, the Hg / HgO electrode (immersed in 1.0 M KOH solution) is used as the reference electrode, and the electrolyte used is a potassium hydroxide solution containing cyclohexanone (1 M KOH + 0.1 M cyclohexanone).

[0172] Before each electrochemical data acquisition, the solution resistance (R s ) values, the CV curves were scanned multiple times in the voltage range of 0.1-0.9V vs.Hg / HgO until they were stable, and then the LSV test was carried out in the voltage range of 0-1.0V vs.Hg / HgO, and the LSV curve was compensated for 95% IR, and the potential value E(Hg / HgO) was converted to E(RHE) according to the formula E(RHE)=E(Hg / HgO)+0.0977+0.05916×pH. In addition, the CYCOR performance of the material was tested for 4 hours by chronoamperometry (CA test), and the electrolyte after the CA test was quantitatively analyzed by GC. Specific test process: After the CA test is completed, 2mL of electrolyte is drawn out with a syringe and injected into a certain amount of deionized water for dilution, and then a small amount of 1M HCl is added to adjust the pH value of the solution, and then dichloromethane is added for extraction, the organic phase is transferred to a sample bottle, and a small amount of Na 2 SO 4 For dehydration, take 2 μL of sample and inject it into the injector. GC test parameters: detector is FID detector, chromatographic column is DB-5ms capillary column, carrier gas is N 2 The injection port temperature was 250°C, the FID detector temperature was 300°C, and the H 2 Flow rate 30mL / min, air flow rate 400mL / min, tail blow N 2Flow rate: 25 mL / min. Qualitative analysis will be carried out using GC-MS subsequently.

[0173] This application example tested the CYCOR performance of Example 6 (AlF / NiCoSc-OH-C 60 ) and Comparative Example 8 (AlF / NiCoSc-OH). The LSV results are shown in Fig.12 . As can be seen from the figure, for the CYCOR performance, the AlF / NiCoSc-OH-C 60 nanoarray material has a smaller E 50 , and the E 50 vs. RHE are 1.434 V for AlF / NiCoSc-OH-C 60 (1.434 V) < 1.579 V for AlF / NiCoSc-OH, preliminarily indicating that the nanoarray material prepared in the example of the present invention has better CYCOR performance.

[0174] According to HPLC tests, the adipic acid production rate of Example 6 (AlF / NiCoSc-OH-C 60 ) is 0.068 mmol / (h·cm 2 ) at 1.45 V vs. RHE, and the Faraday efficiency is 90.3%; the adipic acid production rate of Comparative Example 8 (AlF / NiCoSc-OH) is 0.042 mmol / (h·cm 2 ) at 1.45 V vs. RHE, and the Faraday efficiency is 57.1%. According to the above performance results, it can be seen that the HMFOR performance of Example 6 (AlF / NiCoSc-OH-C 60 ) is better than that of Comparative Example 8 (AlF / NiCoSc-OH).

[0175] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.

Claims

1. A method for preparing a fullerene-modified transition metal hydroxide nanoarray material, characterized in that: The following steps are involved: S1. Preparation of transition metal hydroxide nanoarrays; S2. placing the transition metal hydroxide nanoarray obtained in step S1 in an amino-containing silane coupling agent solution for grafting modification and post-treatment to obtain a transition metal hydroxide nanoarray material with surface amino modification; S3. placing the amino-modified transition metal hydroxide nanoarray material obtained in step S2 in a fullerene-containing solvent, performing fullerene modification, and post-processing to obtain a fullerene-modified transition metal hydroxide nanoarray material.

2. The preparation method according to claim 1, characterized in that: The specific steps of preparing the transition metal hydroxide nanoarray are: placing the current collector in a mixed solution containing a transition metal salt and a precipitant, performing a solvent thermal reaction, and post-processing to obtain the transition metal hydroxide nanoarray.

3. The preparation method according to claim 2, characterized in that: The transition metal in the transition metal salt is selected from one or more of Ni, Fe, Co, Cu, Zn, Mn, Mo, V, Ce, W, Ti, Zr, Cr, Sc, and Y.

4. The preparation method according to claim 2, characterized in that: The temperature of the solvent thermal reaction is 50-250°C.

5. The preparation method according to claim 1, characterized in that: In step S2, the amino-containing silane coupling agent is selected from at least one of 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, aminoethylaminomethyltriethoxysilane, aminoethylaminopropyltrimethoxysilane, aminoethylaminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, aminohexylaminomethyltrimethoxysilane, methylaminopropyltrimethoxysilane, 3-aminopropylmethyldiethoxysilane, aminoethylaminopropylmethyldimethoxysilane, diethylenetriaminopropylmethyldimethoxysilane, methylaminopropylmethyldiethoxysilane and methylaminomethylmethyldiethoxysilane.

6. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the grafting modification is 25-150°C.

7. The preparation method according to claim 1, characterized in that: In step S3, the fullerene is selected from C 20 , C 60 , C 70 , C 72 , C 76 , C 80 , C 84 , C 96 At least one of .

8. The preparation method according to claim 1, characterized in that: In step S3, the temperature of fullerene modification is 20-150°C.

9. The fullerene-modified transition metal hydroxide nanoarray material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the fullerene-modified transition metal hydroxide nanoarray material according to claim 9 in organic electro-oxidation reactions.

Citation Information

Patent Citations

  • Carbon-modified transition metal-based compound nano array electrode as well as preparation method and application thereof

    CN117431571A

  • Surface-modified heterojunction nano array electrode and preparation method and application thereof

    CN117431584A

  • Method for preparing fe@cumoo 4NWA / cu catalyst and application

    WO2023284064A1

Cited By

  • Fullerene-modified cobalt-based transition metal oxide nano composite material as well as preparation method and application thereof

    CN122082016A

  • Fullerol modified nano array electrode material and preparation method and application thereof

    CN122128755A

  • Fullerol-modified precious metal-based alloy nanocluster material as well as preparation method and application thereof

    CN122141753A